PENGARUH RASIO PROFITABILITAS TERHADAP PERUBAHAN HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI JII - Rafli Dilazare Wicaksono; Kornitasari, Yenny (Islamic Economics and finance in Focus, 2023)
Investors before carrying out investment activities need to analyze the company's financial statements in order to see the company's performance and estimate the company's stock price movements with the aim of benefiting from investment activities. This study aims to determine the effect of Return On Asset, Return On Equity, Earning Per Share and Net Profit Margin on changes in stock prices in companies listed on the Jakarta Islamic Index. The population used in this study are companies that have been listed for 4 consecutive years during the 2018-2021 period on the Jakarta Islamic Index. The data used is secondary data by purposive sampling. The data analysis method in this study is a hypothesis. From this study, it was found that Return On Asset partially had a positive and significant effect on stock prices. While Return On Equity, Earning Per Share and Net Profit Margin partially have a negative and insignificant effect on stock prices. So that from this research, the Return On Asset ratio can be used by investors as a reference to see future stock price movements and the Return On Equity, Earning Per Share and Net Profit Margin ratios cannot be used to analyze stock price movements.